Holodomor - Éhínség Ukrajnában - Hegedüs, István (Hungary : MTV - Hungarian Television, 2008)
Holodomor means the mass starvation of people in Ukrainian. As a consequence of compulsory food requisition and confiscation, measures taken by the Stalinist regime, in Ukraine in the early 1930s at least eight million people, three million of them children, died of starvation in only five hundred days. In addition, generations died off and several million other people suffered damage to their health for the rest of their lives.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films